Clozapine in Treatment-Resistant Bipolar Disorder With Suicidality. Three Case Reports - Wilkowska, Alina; Wiglusz, Mariusz S.; Cubała, Wiesław J. (Frontiers in Psychiatry, 2019)
Bipolar disorder is associated with a high risk of suicide attempts and suicide deaths. The suicide mortality of people with bipolar disorder is approximately 25 times higher than the general population. No approved pharmacological strategies for suicidal thoughts and attempts in bipolar disorder have been introduced so far, and lithium remains as the first-line treatment for suicidal subjects. Clozapine is also a potentially good candidate for this indication. This case series represents three treatment-resistant bipolar patients with severe suicidal ideation who responded to low-dose clozapine treatment.